Acts of Spatial Violation: The Politics of Space-Making inside the Palestinian Refugee Camp. Issue 1 (16th November 2021) - Maqusi, Samar
Refugee camps have been, and continue to be, highly polemical spaces to inhabit and study. Notions such as temporality, permanence, exception and camp-cities are used in academic publications in an attempt to understand the continued existence of these spaces. Scholars nonetheless have fallen short of presenting a historical narrative, or convincing argument, as to why and how these camps can ensure their continued operation within often violent and complex host geographies. Refugee camps are not merely humanitarian spaces relegated to international aid programmes. On the contrary, due to their common protracted nature, they have evolved into some of the most dynamic and vital forms of built environment. The fundamental element which guarantees this vitalism, in socio-economic and political terms, is space and space-making. This essay, based on long-term fieldwork research in two Palestinian refugee camps – Baqa'a in Jordan and Burj el Barajneh in Lebanon –showcases the specific ingenious acts of space-making developed by Palestinian refugees throughout 73 years of forced displacement. Furthermore, the essay introduces the notion of 'spatial violations' to describe the political act of space-making adopted by Palestinian refugees to overcome modes of 'management and control' by host governments and the United Nations. Scenarios of violence and economic development triggered by these acts of 'spatial violation' will also be illustrated, as will some spatial interventions designed and built inside these two Palestinian camps as part of this research project. The installations were designed as experiential architectural devices to provoke conversation around space and space-making across Palestinian camps.